Cancellation exponents and multifractal scaling laws in the solar wind magnetohydrodynamic turbulence - V. Carbone (Annales Geophysicae)
Some signed measures in turbulence are found to be sign-singular, that is their sign reverses continuously on arbitrary finer scales with a reduction of the cancellation between positive and negative contributions. The strength of the singularity is characterized by a scaling exponent κ, the cancellation exponent. In the present study by using some turbulent samples of the velocity field obtained from spacecraft measurements in the interplanetary medium, we show that sign-singularity is present everywhere in low-frequency turbulent samples. The cancellation exponent can be related to the characteristic scaling laws of turbulence. Differences in the values of κ, calculated in both high- and low-speed streams, allow us to outline some physical differences in the samples with different velocities.